Hubungan Komunikasi Interpersonal Pelatih terhadap Peak Performance Atlet Pencak Silat SMI Bukittinggi - Fitria Rahmadani; Prima Aulia (Balai Diklat Keagamaan Semarang, 2023)
This study aims to look at the relationship of coach interpersonal communication with peak performance in pencak silat athletes SMI Bukittinggi. The research is using quantitative correlational design. The population of this study is pencak silat athletes in SMI Bukittinggi. The sampling method is using purposive sampling technique with a sample of 54 pencak silat athletes. Data collection is by means of the scale of communication interpersonal and scale of peak performance. Data analysis use Karl Pearson’s Product Moment Correlation. The results of this study indicated that there is a significant positive relationship between communication interpersonal and peak performance in pencak silat athletes in SMI Bukittinggi with a correlation value of r_xy= .370 and p= .006 (p<.05), which indicates that the higher coach interpersonal communication, the level of peak performance becomes higher and otherwise if interpersonal communication is low then the peak performance level is low.